Reefense: Living shoreline mosaics can achieve ecological and engineering outcomes with interdisciplinary design - Rebecca L. Morris; Jaden E. Akers; Sandra Casas; Justin Geldard; Alex Goad; Marco Ghisalberti; Ximing Guo; Reid Holland; Hongyue Jin; Kelly M. Kibler; Danielle Kreeger; Brendan S. Lanham; et al. (Proceedings of the National Academy of Sciences, 2026)
Living shorelines that comprise oyster reefs within a mosaic of multiple coastal habitats can be a resilient and adaptive coastal protection alternative to conventional engineered structures. The success of an oyster reef living shoreline depends on the evolution of a stable base substrate that provides initial short-term coastal protection, to the growth of a living oyster reef and associated habitats in the longer-term, which can enhance protection and provide other ecosystem services. Interdisciplinary global teams that include ecologists, biologists, engineers, techno-economists, and industry are leading the development and implementation of innovative reef-based coastal protection (“Reefense”) solutions that can be scaled to face the challenges of climate change.